Sistem Pendukung Keputusan Penerimaan Beasiswa Berprestasi Pada Perguruan Tinggi Swasta Menerapkan Metode Waspas - Zulkifli Zulkifli (STMIK Budi Darma, 2021)
Scholarship recipients at the Regional Education Council are carried out by giving scholarship receipts still using a simple method so that it can lead to data manipulation. Those who should receive scholarships may not be on target due to errors in calculating criteria that are less effective. For this reason, a decision support system is needed to assist the calculation of existing alternatives and the method used in the calculation is the Wheight Aagreated Sum Assessment Product or also known as WASPAS. This system is a Decision Support System (DSS) which was built using the WASPAS method and designed using Microsoft Visual Studio 2008. The research carried out has succeeded in developing the system with all its advantages and disadvantages so that it can be utilized and it can be concluded that the research problems that have been carried out previously. According to the author, the wasapas method can answer the problems that the writer is researching, can compare the rankings and help the selection team in comparing the rankings obtained to select outstanding scholarships at the Regional Education Council Office of Subulussalam City.